Local Application of Sodium Salicylate Enhances Auditory Responses in the Rat’s Dorsal Cortex of the Inferior Colliculus - Patel, Chirag R.; Zhang, Huiming (Frontiers in Neurology, 2014)
Sodium salicylate is a widely used medication with side effects on hearing. In order to understand these side effects, we recorded sound-driven local field potentials in a neural structure, the dorsal cortex of the inferior colliculus (ICd). Using a microiontophoretic technique, we applied sodium salicylate at sites of recording and studied how auditory responses were affected by the drug. Furthermore, we studied how the responses were affected by combined local application of sodium salicylate and an agonists/antagonist of the type-A or type-B γ-aminobutyric acid receptor (GABAA or GABAB receptor). Results revealed that sodium salicylate applied alone enhanced auditory responses in the ICd, indicating that the drug had local targets in the structure. Simultaneous application of the drug and a GABAergic receptor antagonist synergistically enhanced amplitudes of responses. The synergistic interaction between sodium salicylate and a GABAA receptor antagonist had a relatively early start in reference to the onset of acoustic stimulation and the duration of this interaction was independent of sound intensity. The interaction between sodium salicylate and a GABAB receptor antagonist had a relatively late start, and the duration of this interaction was dependent on sound intensity. Simultaneous application of the drug and a GABAergic receptor agonist produced an effect different from the sum of effects produced by the two drugs released individually. These differences between simultaneous and individual drug applications suggest that sodium salicylate modified GABAergic inhibition in the ICd. Our results indicate that sodium salicylate can affect sound-driven activity in the ICd by modulating local GABAergic inhibition.